2007
DOI: 10.1113/jphysiol.2007.141051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the menstrual cycle on sympathetic neural responses to mental stress in humans

Abstract: The influence of the menstrual cycle on resting muscle sympathetic nerve activity (MSNA) remains controversial, and the effect of the menstrual cycle on MSNA responses to mental stress is unknown. We examined MSNA, mean arterial pressure (MAP), and heart rate (HR) responses to mental stress (via mental arithmetic) in 11 healthy females during the early follicular (EF) and mid-luteal (ML) phases of the menstrual cycle. The menstrual cycle did not alter resting MSNA (EF, 13 ± 3 bursts min −1 versus ML, 13 ± 2 bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
42
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 35 publications
9
42
1
Order By: Relevance
“…The present study did not notice any differences in the basal heart rate between the phases, which is similar to the findings of many other studies [17][18][19][20]. Similarly the insignificant differences in basal SBP and DBP values in this study were also in concordance with the findings of Sato et al, [11].…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The present study did not notice any differences in the basal heart rate between the phases, which is similar to the findings of many other studies [17][18][19][20]. Similarly the insignificant differences in basal SBP and DBP values in this study were also in concordance with the findings of Sato et al, [11].…”
Section: Resultssupporting
confidence: 83%
“…Unlike this, the results in the present study did not show significant variations in cardiovascular reactivity to mental stress between two phases of the menstrual cycle. Similar observations regarding cardiovascular reactivity to stress were also observed by few previous studies [12,13,17] but with a lesser sample size than present study. These observations regarding stress induced cardiovascular reactivity and menstrual cycle in various other studies are provided in [Table /Fig-4].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…[ [15][16][17] In the same line, a few studies have also reported insignificant differences in the mean arterial pressure. [16,18] This has been suggested to be because the changes in hypothalamic pituitary ovarian axis functioning over the course of the menstrual cycle are barely reflected in resting parameters and which may become prominent when the system is activated by a potent stressor.…”
Section: Discussionsupporting
confidence: 49%
“…[15][16][17][18][19] The definitive interaction of these physiological characteristics is very meagerly found in literature search, particularly in young Indian females. The results of studies conducted in women, examining the response of experimentally induced noxious stimulation and its variations related to the menstrual phase, did not showed conclusive findings.…”
mentioning
confidence: 99%